ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKN DI SMK NEGERI 1 LAHOMI - Bober Rindis Mahenda Zebua (Universitas Nias Raya, 2025)
Learning media is a tool used by a teacher in the teaching and learning process to attract students' interest and attention to learning. Therefore, as a teacher you must be able to use learning media so that the learning process can be carried out effectively. The aim of this research is how to use learning media to improve student learning outcomes in Civics subjects at SMK Negeri 1 Lahomi. This research is qualitative research using a descriptive approach. The type of data in this research is primary data which is data obtained from the learning process carried out by PPKn teachers at SMK Negeri 1 Lahomi. Then, the data collection techniques used by researchers are observation, interviews and documentation. Furthermore, the data analysis technique used is using Sugyono's theory (2013:246), including; data reduction, data display, conclusion/verification. Based on the research findings and discussion in this study, the researcher can conclude that the learning media used by PPKn teachers at SMK Negeri 1 Lahomi are visual media, including; print media/books, laptops, and infocus/projectors and image media/maps. By using these learning media, the learning process can be followed by students so that the teaching and learning process can be carried out effectively and efficiently. Therefore, it can influence the improvement of student learning outcomes, characterized by student activity and can be seen from the test scores given by the teacher. Based on this, researchers provide suggestions so that teachers in schools can have creativity in using learning media in the teaching and learning process.